Jessica Martin, The Eucharist in Four Dimensions: The Meanings of Communion in Contemporary Culture (Norwich: Canterbury Press, 2023) - Douglas, Brian (Journal of Anglican studies, 2025)
Jessica Martin, The Eucharist in Four Dimensions: The Meanings of Communion in Contemporary Culture (Norwich: Canterbury Press, 2023). - Volume 23 Issue 1